Early Childhood Language Transformation: is Steam (Science, Technology, Engineering, Art, and Mathematics) Learning The Key to Improving Language Skills? - Ramadani, Fitria; Nisa', Titin Faridatun; Tri Ariyanto, Fajar Luqman; Anawaty, Mardiyana Faridhatul (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This study is motivated by some children who experience barriers in language skills so it needs to be stimulated. This study aims to determine the effect of the STEAM (Science, Technology, Engineering, Art, and Mathematics) approach on the language skills of group B children. Language skills in this study include receptive and expressive abilities of children. This research was conducted with a quantitative approach through the experimental method of pre-Experimental design (One- Group Pretest-Posttest Design) with a research sample of 30 children in group B TKIT YAKHOLQI. For data collection, researchers used interview, observation, and documentation techniques. In data analysis, researchers used the paired sample T-test analysis technique to test the hypothesis with the prerequisites of normality test and homogeneity test. Based on the results of the study, it shows that the results of the paired sample T-test hypothesis test Sig. (2-tailed) 0.000 0.05, which can be concluded that H0 is rejected and Ha is accepted, which means that the application of the STEAM approach has a significant effect on the language skills of children in group B TKIT YAKHOLQI. The STEAM approach in stimulating children's language skills by mentioning, asking, understanding, and communicating the activities that have been carried out.